Impacts of climate events on life history parameters of major commercial fishes in the Beibu Gulf, South China Sea in the last 15 years - Hong, Xiaofan; Zhang, Kui; Li, Jiajun; Xu, Youwei; Sun, Mingshuai; Jiang, Jingyuan; Xu, Shannan; Cai, Yancong; Qiu, Yongsong; Chen, Zuozhi (Frontiers in Marine Science, 2023)
A detailed understanding of the impact of climate variability on fish life histories provides a fundamental basis for the ecosystem approach to fisheries management. In this study, we evaluated the relationship between fish life-history trait parameters and climate periods, using survey data from 2006−2020 for the Beibu Gulf of the northwestern South China Sea, a fishing ground with high commercial and ecological value. We show that climate events can significantly alter the structure of the life history for major commercial fishes, with more diverse life-history strategies during warm events and more concentrated mortality during cold events. Additionally, we detected special relationships between climate events and the life-history trait composite index (LTCI) in Psenopsis anomala and Trichiurus lepturus. It is possible that other indicators would be more appropriate than variability in Oceanic Niño Index (ONI), such as variation in fishing effort or the environmental resistance of fish. Anthropogenic disturbance and biological features may also help explain the magnitude of population variability. We found that changes in life-history traits of only a few commercial fishes (Decapterus maruadsi, Pennahia macrocephalus, and Upeneus sulphureus) were related to the shift in climate periods; these fishes were generally characterized by faster growth and higher mortality rates in the normal and El Niño periods, with the opposite trends in La Niña periods. However, the emergence of climate events has led to a clear complementarity of life-history strategies among some fish in the same ecological niche (same genus and/or feeding group), which may be explained by a balance between habitat conditions and fishing pressures. This study of fish life-history strategies under climate anomalies provides key insights into important attributes for managers to consider when implementing relevant measures to promote fisheries sustainability in the subtropical bay.